Phonology - Josipović Smojver, Višnja (Array, 2009)
Phonology is a branch of linguistics dealing with the function and organization of speech sounds within particular languages and in human language in general. It is closely related to phonetics, another discipline dealing with speech sounds, but differs from it by focusing on the principles that govern the way sounds are organized in languages, rather than dealing with the physical aspect of speech production, transmission and perception. Phonology analyses language in terms of functional units of sound, including sound segments (in earlier approaches known as phonemes) and studies their organization into larger units, such as syllables, phonological words, phrases, and utterances. It expresses rules governing variation in pronunciation, thus searching for significant generalizations about the systems of particular languages and, ultimately, about sound systems in general. Phonology expresses rules of sound-patterning in terms of the so-called distinctive features. Apart from segmental features, such as voicing, or nasalization, phonology also deals with the function of the so-called suprasegmentals in languages, features pertaining to units larger than individual segments. These include properties such as rhythm, intonation, or stress, which are all used in language-specific ways in particular languages. Focusing on the abstract system of language, rather than its physical realization through speech, phonology is necessarily rather abstract. Patterns of sound organization in language are expressed by 'models', i.e., metaphorical representations of what the sound system looks like in human mind and how it functions. These models vary a lot, depending on the particular school of thought which the phonologist subscribes to. Roughly, three major types of analytical framework have been deeply influential in the history of modern phonology, i.e. since the full establishment of linguistics as an independent scientific discipline at the beginning of the 20th century. These are: structuralism, generative (derivational) phonology, including linear and non-linear models, and optimality theory.